KERAPATAN DAN VIABILITAS SPORA BEAUVERIA BASSIANA (BALS.) AKIBAT SUBKULTUR DAN PENGAYAAN MEDIA, SERTA VIRULENSINYA TERHADAP LARVA PLUTELLA XYLOSTELLA (LINN.) - Siti Herlinda, Muhamad Darma Utama, Yulia Pujiastuti, dan Suwandi . (Universitas Lampung, 2006)
Density and viability of spores of Beauveria bassiana (Bals.) Vuill. due to sub-cultures and media enriched, and its virulence against larvae of Plutella xylostella (Linn.) This laboratory research was conducted to determine density and viability of spores of Beauveria bassiana due to sub-cultures and media enriched, and to investigate the fungi virulence againts larvae of Plutella xylostella. B. bassiana was grown in Saborroud Dextrose Broth (SDB) cultures enriched with cricket powder. The results showed that the best sub-culture was the fourth sub-culture enriched with cricket powder, producing 6.05 x 108 spores/ml with 30.7% viability. The highest larval mortality was found in the second sub-culture enriched with cricket powder which was reach 78.33%. The spore density and viability, and virulence of B. bassiana grown in sub-culture without cricket powder enrichment was consistently decreasing from the second sub-culture to the eighth. Sub-cultures enriched with cricket powder could increase density, viability, and virulence of B. bassiana in every sub-culture. Overall, the enrichment with cricket powder up to 0.5% could increase the density, viability, and virulence of B. bassiana.